A novel signature to guide osteosarcoma prognosis and immune microenvironment: Cuproptosis-related lncRNA - Yang, Mingyi; Zheng, Haishi; Xu, Ke; Yuan, Qiling; Aihaiti, Yirixaiti; Cai, Yongsong; Xu, Peng (Frontiers in Immunology, 2022)
Objective: Osteosarcoma(OS) is a common bone malignancy with poor prognosis. We aimed to investigate the relationship between cuproptosis-related lncRNAs (CRLncs) and the survival outcomes of patients with OS. Methods: Transcriptome data and clinical data of 86 patients with OS were downloaded from TCGA. The GSE16088 dataset was downloaded from the GEO database. The 10 cuproptosis-related genes (CRGs) were obtained from a recently published article on cuproptosis in Science. Combined analysis of OS transcriptome data and the GSE16088 dataset identified differentially expressed CRGs related to OS; next, pathway enrichment analysis was performed. Co-expression analysis obtained CRLncs related to OS. Univariate COX and LASSO regression analysis were used to construct the risk prognostic model of CRLncs. Risk curve, survival, receiver operating characteristic (ROC) curve, and independent prognostic analyses were performed. Next, principal component analysis (PCA) and t-distributed stochastic neighbor embedding (t-SNE) analysis were performed. Single-sample gene set enrichment analysis (ssGSEA) was used to explore the correlation between the risk prognostic models and OS immune microenvironment. Drug sensitivity analysis identified drugs with potential efficacy in OS. Real-time quantitative PCR, western blotting, and immunohistochemical analyses verified the expression of CRGs and CRLncs. Results: Six CRLncs that can guide OS prognosis and immune microenvironment were obtained, including three high-risk CRLncs (AL645608.6, AL591767.1, and UNC5B-AS1) and three low-risk CRLncs (CARD8-AS1, AC098487.1, and AC005041.3). Immune cells such as B cells, macrophages, T helper type 2 (Th2) cells, regulatory T cells (Treg), and immune functions such as APC co-inhibition, checkpoint, and T cell co-inhibition were significantly downregulated in high-risk groups; in addition, we obtained four drugs with potential efficacy for OS: AUY922, bortezomib, lenalidomide, and Z.LLNle.CHO. The expression of LIPT1, DLAT, and FDX1 at both mRNA and protein levels was significantly elevated in OS cell lines compared with normal osteoblast hFOB1.19. The mRNA expression level of AL591767.1 was decreased in OS, AL645608.6, CARD8-AS1, AC005041.3, AC098487.1 and UNC5B-AS1 was up-regulated in OS.Conclusion: CRLncs that can guide OS prognosis and the immune microenvironment and drugs that may have a potential curative effect on OS obtained in this study provide a theoretical basis for OS survival research and clinical decision-making.